2005
DOI: 10.1037/0278-6133.24.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Posttraumatic Growth Following Bone Marrow Transplantation for Cancer.

Abstract: There is growing recognition that the experience of cancer can have a positive as well as a negative psychological impact. This longitudinal study sought to identify predictors of posttraumatic growth among cancer patients (N ϭ 72) undergoing bone marrow transplantation. Greater posttraumatic growth in the posttransplant period was related to younger age; less education; greater use of positive reinterpretation, problem solving, and seeking alternative rewards as coping strategies in the pretransplant period; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
246
13
24

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(326 citation statements)
references
References 39 publications
43
246
13
24
Order By: Relevance
“…Posttraumatic growth has been positively associated with social support, active coping, and participation in leisure activities [53][54][55][56][57]. The results of a thematic analysis revealed that leisure influenced at least four aspects of life experiences related to growth: 1) providing opportunities to find personal strengths and abilities, 2) building companionship and meaningful relationships, 3) making sense of traumatic experience and finding meaning in everyday life, and 4) generating positive emotions.…”
Section: Post-traumatic Growthmentioning
confidence: 96%
“…Posttraumatic growth has been positively associated with social support, active coping, and participation in leisure activities [53][54][55][56][57]. The results of a thematic analysis revealed that leisure influenced at least four aspects of life experiences related to growth: 1) providing opportunities to find personal strengths and abilities, 2) building companionship and meaningful relationships, 3) making sense of traumatic experience and finding meaning in everyday life, and 4) generating positive emotions.…”
Section: Post-traumatic Growthmentioning
confidence: 96%
“…20,[62][63][64][65][66] Specifically, patientreported benefits include an enhanced appreciation for life, different priorities, love and appreciation for family and friends, and greater religious or spiritual beliefs. 20,64,65 Reported benefits are unrelated to physical functioning and other QOL indices. 20,66 These data suggest that patients are often able to reinterpret the adversity of HCT into a meaningful life narrative despite reduced QOL.…”
Section: Patient-reported Benefits Of Hctmentioning
confidence: 99%
“…A legtöbb kutatásban a nem professzionális társas támogatás (Widows, Jacobsen, Booth-Jones, & Fields, 2005;Zwahlen és mtsai, 2010) és az önfeltárás (Lev-Wiesel & Amir, 2003;Posta, 2010;Taku, Tedeschi, Cann, & Calhoun, 2009) is növekedést facilitáló tényezônek bizonyult, bár egyes vizsgálatok nem találtak ilyen irányú összefüggést (Cordova, Cunningham, Carlson, & Andrykowsky, 2001). A személyiségvonások közül a rugalmasság (Posta, 2010;Bossick, 2009), diszpozicionális optimizmus (Posta, 2010;Bossick, 2009), extraverzió, nyitottság (Tedeschi & Calhoun, 1996), koherenciaérzés, szívósság (Bossick, 2009) Maercker, 2006).…”
Section: Bevezetésunclassified